Evaluation of chitosan nanoformulations as potent anti-HIV therapeutic systems - Ramana, Lakshmi Narashimhan; Sharma, Shilpee; Sethuraman, Swaminathan; Ranga, Udaykumar; Krishnan, Uma Maheswari (Biochimica et biophysica acta, 2014)
Antiretroviral Therapy (ART) is currently the major therapeutic intervention in the treatment of AIDS. ART, however, is severely limited due to poor availability, high cytotoxicity, and enhanced metabolism and clearance of the drug molecules by the renal system. The use of nanocarriers encapsulating the anti-retroviral drugs may provide a solution to the aforementioned problems. Importantly, the application of mildly immunogenic polymeric carrier confers the advantage of making the nanoparticles more visible to the immune system leading to their efficient uptake by the phagocytes. The saquinavir-loaded chitosan nanoparticles were characterized by transmission electron microscopy and differential scanning calorimetry and analyzed for the encapsulation efficiency, swelling characteristics, particle size properties, and the zeta potential. Furthermore, cellular uptake of the chitosan nanocarriers was evaluated using confocal microscopy and Flow cytometry. The antiviral efficacy was quantified using viral infection of the target cells. Using novel chitosan carriers loaded with saquinavir, a protease inhibitor, we demonstrate a drug encapsulation efficiency of 75% and cell targeting efficiency greater than 92%. As compared to the soluble drug control, the saquinavir-loaded chitosan carriers caused superior control of the viral proliferation as measured by using two different viral strains, NL4-3 and Indie-C1, and two different target T-cells, Jurkat and CEM-CCR5. Chitosan nanoparticles loaded with saquinavir were characterized and they demonstrated superior drug loading potential with greater cell targeting efficiency leading to efficient control of the viral proliferation in target T-cells. Our data ascertain the potential of chitosan nanocarriers as novel vehicles for HIV-1 therapeutics. •Higher encapsulation of the drug saquinavir•Better cell uptake of the carrier using FACS•Greater viral load reduction at the nanogram level of drug formulation•Shows viral reduction up to 82% in both the subtypes of virus